Molecular Dynamic Simulation of the Patchouli Oil Extraction Process - Fatmawati, Adam; Siti Hana, A. B.; M. M., Yusoff; Saiful Nizam, Tajuddin (ACS Publications, 2014)
Patchouli is a plant which is native in Malaysia. It is an economic crop, planted for its essential oil. Patchouli oil has a characteristic woody scent and is used commercially as an ingredient in fragrance and cosmetic products. The average yearly consumption around the globe is around one metric ton. A marker compound responsible for the patchouli oil scent is patchoulol (C15H26O). It is the major compound in patchouli oil representing around 40–50% of the essential oil composition. The aim of this study is to simulate the patchouli oil extraction process using patchoulol as a modeled molecule in different solvents, namely acetone, ethanol, and hexane. The simulation aim is to recognize molecular interaction between patchoulol molecules with solvent molecules through hydrogen bonding and also the repulsion forces between them due to the abundance of hydrogen atoms in the patchoulol molecule. The simulation is equilibrated under moles, volume, and energy followed by moles, pressure, and temperature ensembles via molecular dynamics simulation using the Material Studio software package. The interaction in the system is analyzed through the radial distribution function to describe the structure of patchoulol in solvent solution. The rdf trend found that the interaction between patchoulol solutes is through the oxygen atom (O1P) and hydrogen (H1P) atom from the hydroxyl functional group of the patchoulol molecule. In the acetone–patchoulol and hexane–patchoulol systems, the patchoulol solutes tend to self-agglomerate indicated by first neighboring molecules in the range of 4.25 Å and 5.75 Å, respectively, while the first neighboring molecules of patchoulol solutes in the binary ethanol–patchoulol system is located at 7.75 Å. This might suggest that the patchoulol is much more soluble in ethanol then in acetone and hexane. The pattern observed in the simulations is in agreement with extraction yield results obtained from the extraction experiment.